1983
DOI: 10.1002/jrs.1250140308
|View full text |Cite
|
Sign up to set email alerts
|

A Raman spectroscopic study of the structural phase transition and reorientational motions of the ClO ions in KClO4

Abstract: Polarized Raman spectra of oriented single crystals of KCIO, performed over a large temperature range (300-800 K) have been used to investigate the mechanism of the 583 K phase transition. It is shown that the transition can be described using an order parameter and a mechanism based on the reorientation of the Clodions is proposed. A Raman study of the plastic phase (above 583 K), using the shape of the bands associated with the internal modes, leads to a measure of the orientational density probability and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0
1

Year Published

1986
1986
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 11 publications
3
22
0
1
Order By: Relevance
“…The authors concluded that when going from the less symmetric to the more symmetric phase, the strong "rst-order character of the transition impedes any relationship between the two structures. A direct observation of the phase transition on a microscopic scale from our simulation shows that the transition in KClO follows the simple mechanism proposed by Toupry et al (9). The simulation based on the classical potentials and a rigid-molecule model obtained the same result (18).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The authors concluded that when going from the less symmetric to the more symmetric phase, the strong "rst-order character of the transition impedes any relationship between the two structures. A direct observation of the phase transition on a microscopic scale from our simulation shows that the transition in KClO follows the simple mechanism proposed by Toupry et al (9). The simulation based on the classical potentials and a rigid-molecule model obtained the same result (18).…”
Section: Discussionsupporting
confidence: 84%
“…To explain Raman light scattering of KClO , Toupry et al (9) proposed a model with the relationship between the low and high temperature crystal axes shown in Fig. 9a.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, to be more definite, we assigned the following coordinate indexes to the components of the 133Cs EFG tensor calculated according to (4) ( …”
Section: ( 5 )mentioning
confidence: 99%
“…The transition is connected with an abrupt change in the volume (approximately 10%) and a considerable temperature hysteresis [2]. On the basis of X-ray [3], Rarnan [4], and dielectric measurements [5] the phase transition is related to an orientational ordering of the anions ClO, in both phases. The recent investigation of the temperature dependence of birefringence and optical microscopic properties of single crystals of potassium, rubidium, and cesium perchlorates has shown that there is no range of coexistence of the two phases [6].…”
Section: Introductionmentioning
confidence: 99%
“…Исследование фазового перехода в перхлоратах важно для понимания механизма и моле-кулярной природы структурных перестроек в твердых телах [33]. В литературе мало данных, посвященных исследованиям именно этого класса ионных соедине-ний [34][35][36][37][38][39]. Поэтому исследование реориентационной подвижности и процессов разупорядочения анионов в области полиморфных превращений в перхлоратах щелочных металлов методом КР является актуальной задачей.…”
Section: Introductionunclassified